Context Document [Tunisia]: Context Assessment for Agroecology Transformation in the Tunisian Living Landscape - Alary, Veronique; Frija, Aymen; Ouerghemmi, Hassen; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad; Souissi, Asma; Dhehibi, Boubaker; Bahri, Haithem; Mekki, Insaf; Toukebri, Wael; Barbouchi, Meriem; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
The purpose of this Context Assessment is threefold: first, to characterize the environmental, social, economic, and political contexts of the Tunisian Agroecological Living Landscape (ALL); second, to understand the data and information currently available in the sub-region of this ALL; and third, to characterize the extent to which agroecological principles are already being employed locally at the ALL level. This report constitutes a basis of information and discussion to conduct an impact assessment. It is also valuable to all work packages in the CGIAR Initiative on Agroecology as it provides critical quantitative and qualitative data and information regarding capacity assessment, policy influence, and other environmental attributes that can guide the implementation and impact of the Initiative in 2023–2024.